Skin transcriptomic and selection signature analyses identify ASIP as a key gene in cattle coat color determination - Wang, Xin; Xu, Longxin; Zhou, Di; Lv, Yanli; Wu, Junda; Zhao, Yuanfeng; Ni, Mengmeng; Zhou, Wenzhang; Zhang, Kaikai; Wang, Hua; Zhang, Jipan (Frontiers in Genetics, 2025)
ObjectiveCoat color is a complex trait and plays an important role in breed identification. However, information regarding genes associated with coat color in cattle is limited, especially at the skin transcriptome level.MethodsWe investigated the differential expressed genes (DEGs) and genomic selection signal underlying the coat color variation between black and brown cattle breeds. A total of 19 cattle (Brangus, Angus, Simmental, and Guanling) were performed skin transcriptome analysis and 262 cattle (Angus and Simmental) were performed whole genome analysis.ResultsAngus cattle (black coat) had a significantly higher melanin content in both their hair and skin compared to that of Simmental and Guanling cattle (brown coat). Transcriptomic analysis identified 14,118 expressed genes, with principal component analysis and hierarchical clustering revealing clear differences between black and brown cattle. DEGs analysis across four pairwise breed comparisons highlighted 343 downregulated and 54 upregulated genes common to all comparisons, with the ASIP gene (agouti signaling protein) emerging as a key gene linked to melanogenesis. The ASIP expression was several dozen-fold higher in brown cattle than in black cattle, suggesting a crucial role in coat color determination. Path-way enrichment and gene set enrichment analysis (GSEA) identified the “Melanogenesis” pathway as significantly enriched and central to coat color variation. Genes such as FZD10, WNT6, and ASIP showed differential expression patterns that correlated with coat color. Genomic analysis revealed strong selection signals in the ASIP gene region, with several SNPs exhibiting high linkage disequilibrium. Notably, the mutation type was predominant in Simmental cattle, while the reference allele was more common in Angus cattle.ConclusionBased on the skin transcriptomic and genomic analyses, we found that ASIP was significantly differential expressed between black and brown cattle breeds and under strong positive selection. These findings provide valuable insights into the genetic basis of coat color variation in cattle and highlight the ASIP gene as a critical determinant of this trait.